BS EN IEC 61557-13. Electrical safety in low voltage distribution systems up to 1 000 V a.c. and 1 500 V d.c. Equipment for testing, measuring or monitoring of protective measures. Part 13. Hand-held and hand-manipulated current clamps and sensors for measurement of leakage currents in electrical distribution systems (4th June 2021) - British Standards Institution,
No abstract available